Marie Joseph Paul Yves Roch Gilbert Du Motier, marquis de Lafayette, papers - Lafayette, Marie Joseph Paul Yves Roch Gilbert Du Motier, marquis de, 1757-1834.
Correspondence, legal documents, clippings, broadsides, orderly book, photographs, and other papers relating chiefly to Lafayette's military service in Canada and Virginia, his tour of the United States (1824-1825), his land in Florida, and his views on such topics as the slave trade and the French government. Also includes material pertaining to the centennial observance of his death. Correspondents include Thomas Clarkson, George Washington Parke Custis, Mordecai Gist, George Graham, Catherine Littlefield Greene, Abiel Holmes, Charles King, Henry Laurens, Antoine Vaudoyer, Marinus Willett, and William Woodford.
Microfilm edition of selected correspondence available
In part, microfilm, photocopies, and transcripts.
Microfilm of originals in private hands.
Soldier and statesman.
Collection material in French and English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Clarkson, Thomas, -- 1760-1846 -- Correspondence; Custis, George Washington Parke, -- 1781-1857 -- Correspondence; Gist, Mordecai, -- 1742-1792 -- Correspondence; Graham, George, -- 1770-1830 -- Correspondence; Greene, Catherine Littlefield -- Correspondence; Holmes, Abiel, -- 1763-1837 -- Correspondence; King, Charles, -- 1789-1867 -- Correspondence; Laurens, Henry, -- 1724-1792 -- Correspondence; Vaudoyer, Antoine, -- 1756-1846 -- Correspondence; Willett, Marinus, -- 1740-1830 -- Correspondence; Woodford, William, -- 1734-1780 -- Correspondence; Real property -- Florida; Slave trade; Canada -- History -- 1775-1783.; France -- Politics and government; United States -- Description and travel; United States -- History -- Revolution, 1775-1783 -- Campaigns; Virginia -- History -- Revolution, 1775-1783.; Soldiers; Statesmen